International pregnancy loss/ miscarriage day posts shared on Instagram: a content analysisAJOG Global Reports at a Glance - Atikah Sayogo Putri; Achmad Kemal Harzif; Putri Nurbaeti; Aisyah Retno Puspawardani; Nafi'atul Ummah; Shakira Amirah; Muhammad Candrika Agyawisnu Yuwono; Mila Maidarti; Kanadi Sumapraja (AJOG Global Reports)
Background: Miscarriage refers to the loss of a fetus before the completion of 28 weeks of gestation. The prevalence of miscarriage across all age groups ranges from 12% to 20%. Despite the great incidence of miscarriage, public awareness and understanding about pregnancy loss remain inadequate. Currently, social media platforms, such as Instagram, are frequently utilised by the public as a mechanism to address their health-related concerns. Objective: This study aims to determine the characteristics of content disseminated on Instagram regarding International Pregnancy Loss/Miscarriage Day over the preceding three-year period. Study Design: This was an analytical-observational study to describe community participation on Instagram in commemorating International Pregnancy Loss Day 2022-2024. Hashtags used include #pregnancyloss, #pregnancylossawareness, and #pregnancylossjourney. Data were analysed using content analysis and simple nominal descriptive statistics to enable comparison. Results: A total of 600 Instagram posts were deemed eligible and met the specified inclusion criteria for subsequent analysis. The data revealed that the predominant form of content consists of text/quotes, comprising 44.38% (n=248) of the total content. The most common content type was personal experience sharing, accounting for 55.6% (n=334), followed by education/information for 44.24% (n=265). Conclusion: The utilization of social media platforms like Instagram to commemorate International Pregnancy Loss Day, particularly by health care provider, has huge potential benefit to spread awareness, information, as well as providing support for patients.